Entomopathogenic Fungi as potential biocontrol agents of insect pests - Rachana, R R; Richa, V; Akoijam, R; Jayasimha, G T (Indian Farming, 2018)
The application of entomopathogenic fungi in biological control is increasing tremendously because of greater environmental awareness, food safety concerns and the failure of conventional chemicals due to an increasing number of insecticide resistant species. In determining whether the use of entomopathogenic fungi was successful in pest management, it is necessary to consider each case individually and direct comparisons with chemical insecticides are usually inappropriate.